ENHANCING ENERGY EFFICIENCY IN AUTOMOBILES: MODERN TECHNOLOGIES AND FUTURE PROSPECTS - Zamir Khametov; Muhammadyusuf Abdullaev (Web of Journals Publishing, 2024)
Energy efficiency in the automotive industry has become a critical focus in addressing environmental concerns and rising fuel costs. This article explores the latest advancements in energy-efficient technologies, including lightweight materials, hybrid and electric powertrains, and advanced aerodynamics. Additionally, it examines future trends such as regenerative braking systems, vehicle-to-grid (V2G) integration, and artificial intelligence-driven energy management. The study highlights the potential of these innovations to significantly reduce energy consumption while maintaining performance and sustainability. Challenges such as infrastructure limitations, high costs, and consumer acceptance are also discussed, offering a comprehensive view of the industry's roadmap toward a greener future.
Keywords: Energy efficiency, automotive industry, hybrid powertrains, electric vehicles, lightweight materials, aerodynamics, regenerative braking, vehicle-to-grid (V2G), sustainability, AI-driven energy management.